An Implementation of Lipschitz Simple Functions in Computer Algebra System Singular. (1st April 2021) - Liu, Yanan; Binyamin, Muhammad Ahsan; Aslam, Adnan; Arshad, Minahal; Fan, Chengmei; Mahmood, Hassan; Liu, Jia-Bao
Abstract : A complete classification of simple function germs with respect to Lipschitz equivalence over the field of complex numbers ℂ was given by Nguyen et al. The aim of this article is to implement a classifier in terms of easy computable invariants to compute the type of the Lipschitz simple function germs without computing the normal form in the computer algebra system S ingular.